Profitability Analysis Using the Du Pont System Method In the Fast-Moving Consumer Goods (FMCG) Distribution Subsector of Go-Public Company in Period 2017-2021 - Adriel Nathaniel; Bambang Sugiarto; Sri Handayani (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2023)
The aim of this study is to analyze the profitability level of Fast-Moving Consumer Goods companies in the Retail and Distributor of Medicines (D111), Rental and Distributor of Food (D112), and Processed Food Distributors (D222) subsectors listed on the Indonesian Stock Exchange in the period 2017-2021 based on Du Pont system analysis. The Du Pont system is an analysis method used to show the interaction between Net Profit Margin (NPM), Total Asset Turnover (TATO), Return on Asset (ROA) and Equity Multiplier in determining the value of Return on Equity (ROE). This type of research is descriptive quantitative using the Du-Pont analysis method. The method used in this study is judgement sampling. Types of data and data sources use secondary data derived from financial statements published by companies that are samples of research and data from the Stock Exchange of Indonesia. Analysis shows that PT. Tigaraksa Satria Tbk has the highest profitability as a Fast-Moving Consumer Goods subsector distribution company. The company's ROE from 2017 to 2020 is higher than the industry average, by 2019 has increased and decreased by 2021. PT. Wicaksana Overseas International Tbk became a Fast-Moving Consumer Goods subsector distribution company with the lowest profitability performance of the five samples, based on analysis carried out by the company's ROE from 2017 to 2020 experienced a decline below the industry average and by 2021 a decrease slightly above the industrial average.